Community Empowerment Through Community Tourism in Efforts to Develop Tourism in The Village of Kemenuh, Gianyar District (Study on Sumampan Waterfall Tourism) - Ni Luh Putu Dyah Manusuari; Nyoman Diah Utari Dewi (ARRUS Journal of Social Sciences and Humanities, 2023)
The problem faced by Kemenuh Village in developing tourism is that all elements and actors of tourism development are not yet organized. Efforts must be made to overcome these problems through community empowerment programs. This community service aims to empower the community through community-based tourism, aimed at developing tourism in Kemenu village, Gianyar district. The type of research used is qualitative research which uses a descriptive approach to obtain a comprehensive understanding of behavioral phenomena, cognition, motivation, behavior and so on experienced by research subjects. The data sources used are primary data sources and secondary data sources. The implementation of community-based tourism as an effort to develop the Sumapang Waterfall tourist attraction has proven to be very effective. Forms of community participation in the management of Sumapang Waterfall have played an active role, including community participation in the form of ideas in the early stages of establishing the management of Sumapang Waterfall. Large community participation is manifested in the form of a gate that marks the entrance to Sumapang Waterfall. Community participation in the form of energy, namely mutual cooperation activities carried out every week